OGLE-2017-BLG-0406: spitzer microlens parallax reveals Saturn-mass planet orbiting M-dwarf host in the inner galactic disk - Hirao, Yuki; Hundertmark, Markus; Natusch, Tim; Maoz, Dan; McCormick, Jennie; Street, Rachel A.; Tan, Thiam-Guan; Tsapras, Yiannis; Jørgensen, U. G.; Dominik, M.; Bozza, V.; Skottfelt, J.; et al. (The astronomical journal, 2020)
We report the discovery and analysis of the planetary microlensing event OGLE-2017-BLG-0406, which was observed both from the ground and by the Spitzer satellite in a solar orbit. At high magnification, the anomaly in the light curve was densely observed by ground-based-survey and follow-up groups, and it was found to be explained by a planetary lens with a planet/host mass ratio of from the light-curve modeling. The ground-only and Spitzer-“only” data each provide very strong one-dimensional (1D) constraints on the 2D microlens parallax vector . When combined, these yield a precise measurement of and of the masses of the host and planet M planet = 0.41 ± 0.05 M Jup. The system lies at a distance D L = 5.2 ± 0.5 kpc from the Sun toward the Galactic bulge, and the host is more likely to be a disk population star according to the kinematics of the lens. The projected separation of the planet from the host is (i.e., just over twice the snow line). The Galactic-disk kinematics are established in part from a precise measurement of the source proper motion based on OGLE-IV data. By contrast, the Gaia proper-motion measurement of the source suffers from a catastrophic 10σ error.
Gesehen am 14.12.2020